How well do whole exome sequencing results correlate with medical findings? A study of 89 Mayo Clinic Biobank samples - Middha, Sumit; Lindor, Noralane M.; McDonnell, Shannon K.; Olson, Janet E.; Johnson, Kiley J.; Wieben, Eric D.; Farrugia, Gianrico; Cerhan, James R.; Thibodeau, Stephen N. (Frontiers in Genetics, 2015)
Whole Exome Sequencing (WES) is increasingly being used for diagnosis without adequate information on predictive characteristics of reportable variants typically found on any given individual and correlation with clinical phenotype. In this study, we performed WES on 89 deceased individuals (mean age at death 74 years, range 28-93) from the Mayo Clinic Biobank. Significant clinical diagnoses were abstracted from electronic-medical-record via chart review. Variants (Single Nucleotide Variant and insertion/deletion) were filtered based on quality (accuracy >99%, read-depth >20, alternate-allele read-depth >5, minor-allele-frequency <0.1) and available HGMD/OMIM phenotype information. Variants were defined as Tier-1 (nonsense, splice or frame-shifting) and Tier-2 (missense, predicted-damaging) and evaluated in 56 ACMG-reportable genes, 58 cancer-predisposition genes, along with examining overall genotype-phenotype correlations. Following variant filtering, 7046 total variants were identified (~79/person, 644 Tier-1, 6402 Tier-2), 161 among 56 ACMG-reportable genes (~1.8/person, 13 Tier-1, 148 Tier-2), and 115 among 58 cancer-predisposition genes (~1.3/person, 3 Tier-1, 112 Tier-2). The number of variants across 58 cancer-predisposition genes did not differentiate individuals with/without invasive cancer history (P>0.19). Evaluating genotype-phenotype correlations across the exome, 202 (3%) of 7046 filtered variants had some evidence for phenotypic correlation in medical-records, while 3710 (53%) variants had no phenotypic correlation. The phenotype associated with the remaining 44% could not be assessed from a typical medical record review. These data highlight significant continued challenges in the ability to extract medically meaningful predictive results from WES.